Trajectory optimization on manifolds with applications to quadrotor systems. (March 2020) - Watterson, Michael; Liu, Sikang; Sun, Ke; Smith, Trey; Kumar, Vijay
Manifolds are used in almost all robotics applications even if they are not modeled explicitly. We propose a differential geometric approach for optimizing trajectories on a Riemannian manifold with obstacles. The optimization problem depends on a metric and collision function specific to a manifold. We then propose our safe corridor on manifolds (SCM) method of computationally optimizing trajectories for robotics applications via a constrained optimization problem. Our method does not need equality constraints, which eliminates the need to project back to a feasible manifold during optimization. We then demonstrate how this algorithm works on an example problem onSO ( 3 ) and a perception-aware planning example for visual–inertially guided robots navigating in three dimensions. Formulating field of view constraints naturally results in modeling with the manifoldR 3 × S 2, which cannot be modeled as a Lie group. We also demonstrate the example of planning trajectories onSE ( 3 ) for a formation of quadrotors within an obstacle filled environment.